Dynamics of the limnological parameters and zooplankton of La Brava, a shallow lake of the Atuel-Salado-Chadileuvú-Curacó system (La Pampa, Argentina) - del Ponti, Omar (2015)
La Brava is a shallow lake that is different from others of La Pampa, as it is part of the fluvial system of Desaguadero-Atuel-Salado-Chadileuvú-Curacó rivers. However, dams built upstream disrupt runoff, so water only enters when excessive snowfall in the Andes mountains forces the reservoirs to be opened. Once water enters, it is slowly lost through evaporation, which can lead to drying of the lake. As the ecology of La Brava is unknown, the objective of this study was to determine the limnological parameters, density and taxonomic composition of zooplankton during a period that contained water and salinity increased by evaporation. Samples between January 2009 and November 2010 were taken. The maximum depth (2.1 m) was recorded in October 2009 but declined and in November 2010 was 0.66 m. Na+ and Cl- predominated in ionic composition and the salinity rose from 15.83 to 49.89 g.L-1. The mean transparency was 0.65 m (±0.12) and despite the high concentration of nutrients (TP: 6.02 ±2.87; TKN: 11.17 ±5.92 mg.L-1) the phytoplankton chlorophyll-a concentration was reduced (1.29 ±1.27 mg.m-3). One cladoceran, four copepods and eight rotifers were registered. The greatest diversity was observed during the first month, specially provided by rotifers, when the group reached its greatest density (385.8 ind.L-1), especially given by Brachionus plicatilis Müller, 1786. Increasing salinity affects the diversity, so in June and August 2009 the copepod Boeckella gracilis (Daday, 1902) was recorded, later replaced by the halotolerant Boeckella poopoensis Marsh, 1906. October 2009 was the only occasion when the cladoceran Daphnia menucoensis Paggi, 1996 was registered, in low density (5.7 ind.L-1). Despite their differences with other Pampean environments, in La Brava the typical zooplankton association of the center of the country and northern Patagonia was found, but it differs from another lake of Curacó system where only the halophilic anostracan Artemia persimilis Piccinelli & Prosdocimi, 1968 was registered.